Reorientasi Kebijakan Fiskal Daerah dalam Kerangka Desentralisasi Fiskal: Studi pada Pemerintah Kota Kendari - Teguh Permana; Andriani Puspitaningsih (Politeknik Sawunggalih Aji, 2026)
This study examines the reorientation of regional fiscal policy within the framework of fiscal decentralization in the Government of Kendari City using the 2023 regional budget data. The findings reveal that the degree of fiscal decentralization remains relatively low, with locally generated revenue contributing 25.9% of total revenue, while intergovernmental transfers account for 66.7%. Expenditure structure is largely dominated by personnel spending rather than capital expenditure, indicating limited fiscal flexibility to promote productive public investment. Although local revenue growth demonstrates potential to strengthen fiscal autonomy, dependence on central transfers remains substantial. Five-year fiscal projections suggest that the decentralization ratio may improve if local revenue grows faster than transfers. The study highlights the need to optimize local revenue sources and restructure expenditure allocation to enhance sustainable fiscal autonomy.